STRATEGI IMPLEMENTASI UNTUK MENGENDALIKAN KONVERSI LAHAN SAWAH DI KOTA SUKABUMI - Ari Wijayanti; Khursatul Munibah; Eka Intan Kumala Putri (Diponegoro University, 2016)
Paddy land conversion in Sukabumi City is worrying whereas its rate is 6,06 ha annually, while its production is very high that reaches 6.7 ton/ha. The aims of this study are to analyze the total paddy land that had been converted into other uses as well as to formulate strategies to implement this program. The method used are by using overlay land use map year 2010, 2012 and 2015 and combination AHP-SWOT The results show that paddy land that had been converted into other uses as many as 181.94 ha. The main strategies to implement this program are by increasing productivity, developing cooperation between private sector and farmer group, and strengthening its institution.